Integration Of Mandar Local Cultural Values Into The Content Of Arabic Reading Skills Learning/ دمج القيم الثقافية المحلية لقبيلة مَنْدَرْ في محتوى تعليم مهارة القراءة - Gazali, Muhammad; Ainin, Moh. (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
Arabic language learning often focuses on mastering linguistic aspects without considering the socio-cultural context of learners. This research is motivated by the challenge of integrating Mandar's local cultural values into the content of Arabic reading skills learning. Local culture, such as sirondoi (cooperation), sipakatau (mutual respect), and oral traditions like pappasang, kalindaqdaq, and pau-pau, are Mandar cultural values that can enrich the Arabic language learning process, both linguistically and culturally. The purpose of this research is to 1) describe Mandar local cultural values; 2) explain the opinions of Arabic language experts on the integration of Mandar local cultural values into Arabic reading skills learning; 3) propose the design of thematic content for Arabic reading instruction based on Mandar local cultural values, aiming to help students understand Arabic in a broader cultural context. The method used in this research is educational ethnography with a qualitative approach. Data were collected through direct observation, in-depth interviews with students, lecturers/teachers, and community leaders, and analysis of documents related to Arabic language learning content and the Mandar local culture. The research was conducted on students of the Arabic Language Education Study Program at Datokarama Palu University, lecturers/teachers involved in Arabic language learning, and Mandar community leaders. The results of the research show that (1) Mandar local cultural values such as sirondoi, sipakatau, pappasang, kalindaqdaq, and pau-pau can be integrated into the content of Arabic reading skills learning; (2) Arabic language experts/observers believe that these values can be applied in the classroom to encourage students to work together in learning groups, respect each other in communication, both orally and in writing; (3) The design based on these local cultural values can be embedded into Arabic reading instruction content into Arabic reading skills learning. The theoretical conclusion is that integrating Mandar's local cultural values into the content of Arabic reading skills instruction can be offered as a design in Arabic language learning that aims for students to understand language in a broader cultural context, more relevant and meaningful.